Effect of somatostatin on human retinal pigment epithelial cells permeability. (July 2019) - Fonollosa, Alex; Valcarcel, Maria; Salado, Clarisa; Pereiro, Xandra; Vecino, Elena
Abstract: Purpose: To assess the effect of somatostatin (SST) on the permeability of human retinal pigment epithelial cells. Methods: We conducted two experiments, exposing cells from human-fetal retinal pigment epithelium (hfRPE) cultures to vascular endothelial growth factor (VEGF), with or without SST pretreatment, in one, and to hypoxic conditions, again with or without SST pretreatment, in the other. The paracellular permeability of hfRPE was assessed by measuring transepithelial electrical resistance (TER) and fluorescein isothiocyanate-sodium (FITC-sodium) flux. Immunochemistry analysis was used to assess the expression of occludin and Zonula occludens-1(ZO-1). Results: Both VEGF and hypoxia increased permeability of the hfRPE, as measured by TER and tracer flux, and decreased occludin and ZO-1staining, as measured by immunochemistry. Pretreatment of cultures with SST partially counteracted these effects. Conclusions: Somatostatin may play a role in the regulation of permeability across retinal pigment epithelium. It may act as an anti-permeability factor in the retina through the enhancement of tight junction function. Highlights: VEGF and hypoxia increased permeability of the hfRPE, and decreased occludin and ZO-1 expression. SST counteracts hypoxia and VEGF-induced breakdown of barrier function. SST may regulate the outer blood retinal barrier so it might be used to treat conditions characterized by retinal edema.